PREVENTION OF DENTAL CARIES IN THE CONDITIONS OF ECOLOGICAL POLLUTION - I.V. Kovach; H.V. Shtompel; Ye.N. Dychko; A.V. Verbytska (Український стоматологічний альманах)
Modern domestic preventive dentistry has success in the theory of the origin and development of major dental diseases, practice of treatment, including dental caries, and uses these results to prevent children’s diseases in the country.